Migrant cavitation as primary involvement in a particular case of granulomatosis with polyangiitis - Francesco Manti, MD; Caterina Battaglia, MD; Corrado Pelaia, MD; Maria Petullà, MD; Bernardo Bertucci, MD; Domenico Laganà, MD (Radiology Case Reports, 2022)
Granulomatosis with polyangiitis (GPA), previously known as Wegener's granulomatosis, is a necrotizing granulomatous vasculitis of the small and medium vessels involving the upper respiratory tract, lungs, and kidneys. In this case report, we will describe the case of a 60-year-old man who presented to our observation with recurrent episodes of hemoptoe, fever, and mucopurulent sputum. The diagnosis was made by radiological and laboratory tests.